A short note on the left A-Γ-hyperideals in ordered Γ-semihypergroups. Issue 1 (2nd January 2022) - Rao, Yongsheng; Kosari, Saeed; Guan, Hao; Akhoundi, Maryam; Omidi, Saber
Abstract: In this paper, we investigate some properties of left A -Γ-hyperideals and A -( m, n )-Γ-hyperideals in ordered Γ-semihypergroups. The intersection of two left A -Γ-hyperideals need not be a left A -Γ-hyperideal. Also, we present the interesting relationships between Γ-hyperideals and A -Γ-hyperideals in ordered Γ-semihypergroups. Finally, we investigate some properties of the inverse images of left A -Γ-hyperideals. A -( m, n )-Γ-hyperideal.